2018
DOI: 10.3389/fpls.2018.00204
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Cell Physiological Analyses in Different Rice Cultivars Provide New Insights Into Adaptive and Salinity Stress Responses

Abstract: Salinity tolerance has been extensively investigated in recent years due to its agricultural importance. Several features, such as the regulation of ionic transporters and metabolic adjustments, have been identified as salt tolerance hallmarks. Nevertheless, due to the complexity of the trait, the results achieved to date have met with limited success in improving the salt tolerance of rice plants when tested in the field, thus suggesting that a better understanding of the tolerance mechanisms is still require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 83 publications
(107 reference statements)
8
78
0
Order By: Relevance
“…This is in agreement with Formentin et al (2018), who reported that the preactivation of leaf tolerance mechanisms before the onset of ionic stress confers to this cultivar a certain level of salt tolerance. This is in agreement with Formentin et al (2018), who reported that the preactivation of leaf tolerance mechanisms before the onset of ionic stress confers to this cultivar a certain level of salt tolerance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with Formentin et al (2018), who reported that the preactivation of leaf tolerance mechanisms before the onset of ionic stress confers to this cultivar a certain level of salt tolerance. This is in agreement with Formentin et al (2018), who reported that the preactivation of leaf tolerance mechanisms before the onset of ionic stress confers to this cultivar a certain level of salt tolerance.…”
Section: Discussionsupporting
confidence: 93%
“…Baldo did not control Na + uptake as effectively as Vialone Nano, whereas it was more able to tolerate Na + concentration in tissues, in turn supporting crop growth even under salt stress conditions. This is in agreement with Formentin et al (2018), who reported that the preactivation of leaf tolerance mechanisms before the onset of ionic stress confers to this cultivar a certain level of salt tolerance. However, the analysis of panicle biomass data suggested that Baldo could be more susceptible to salt-induced sterility for grain yield, although further experiments are needed to confirm this finding.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Baldo was chosen, not only as being not resistant to imazamox, but also because it was one of the most cultivated rice varieties in Italy, with an economic importance also for the export market [35]. This variety has demonstrated a certain degree of salt tolerance at the seedling stage [36], but only poor information is available on the germination response to salt. The variety CL80 was included as representative of imazamox-resistant varieties.…”
Section: Methodsmentioning
confidence: 99%
“…Rice is considered as most susceptible to salt stress in the seedling, reproductive, and 2-3 leaf stages [6]. Previous investigations clarified that salinity influences rice growth in three phases: osmotic stress, ionic toxicity, and oxidative stress; and salt tolerance is a comprehensive quantitative trait involving both genetic characteristics and physiological responses [7][8][9].…”
Section: Introductionmentioning
confidence: 99%